EXPONENTIAL LEARNING TRAJECTORIES WITH THE CONTEXT OF WORM GROWTH TO SUPPORT STUDENTS’ PROBLEM-SOLVING ABILITIES - Arianti, Yesi; Hiltrimartin, Cecil; -, Meryansumayeka (STKI Harapan Bima, 2025)
TThis study aims to create a problem-solving based learning path for exponential material using the context of worm growth and to determine the effectiveness of this problem-solving based learning path for exponential material utilizing the context of worm growth. Exponential material is often considered difficult by students, so we must be able to create an interesting learning path to assist students in problem-solving, one of which is the PMRI approach. The worms' growth and reproduction process illustrates the exponential concept with an exponential regeneration and growth cycle. This study consists of four activities: (1) Understanding the problem, (2) Developing a plan, (3) Implementing the plan, and (4) Re-examining. The method used in this study is the design research method of the validation study type, which consists of three stages: preparation and design, design experiment, and retrospective analysis. Data collection techniques in this study used observation techniques, interviews, student work results, and pretests/posttests. The results of this study are learning paths designed to provide in-depth conceptual understanding for students and become solutions in problem-solving, especially in exponential material.